Reappraisal of the removable partial denture as a treatment option for the shortened dental arch - Nassani, Mohammad Zakaria; Tarakji, Bassel; Baroudi, Kusai; Sakka, Salah (European Journal of Dentistry, 2013)
For patients with shortened dental arches, many treatment options are available. The existing situation can be maintained by stabilizing the present dentition and improving the occlusion without extending the arch. Alternatively, the shortened dental arch can be extended by either a free-end saddle removable partial denture, cantilevered fixed bridge, or by an implant-supported prosthesis. The free-end saddle removable partial denture can be considered a simple, non-invasive, and relatively cheap treatment option for the shortened dental arch. It was believed that such prosthodontic rehabilitation would be beneficial for the patients in terms of improving oral functions. However, the existing literature indicates that the prognosis of free-end saddle removable partial denture is not predictable, it is problematic, and its contribution to oral functions in patients with shortened dental arches is considered to be dubious. This paper reviews and summarizes the current literature about the outcome of extending the shortened dental arch by a free-end saddle removable partial denture. It also outlines factors that may affect the prognosis of this prosthetic treatment.
Keywords: Free-end saddle; oral functions; partial denture; shortened dental arch; treatment option